Urinary steroid profile in Ironman triathletes - Marcos-Serrano, M.; Olcina, G.; Crespo, C.; Brooks, D.; Timon, R. (Journal of Human Kinetics, 2018)
The aim of this study was to determine variations in the urinary steroid profile of triathletes following an Ironman event. A total of 10 male participants (age = 36.0 ± 1.27 years; body height = 179.29 ± 10.77 cm; body mass = 74.50 ± 1.04 kg) completed an Ironman Championship. Urine samples were collected before, immediately after, and 24 hours following the race. Gas chromatography-mass spectrometry (GC/MS) was used to detect and quantify catabolic and anabolic hormones: Androsterone, Dehydroepiandrosteone (DHEA), Androstenedione and Testosterone (T), Betaestradiol, Estrone, Progesterone, Cortisol (C), Cortisone, Tetrahydrocortisol (THE) and Tetrahydrocortisone (THF). These were measured in their glucuroconjugated and free forms. Androsterone (3297.80 ± 756.83 vs. 2154.26 ± 1375.38), DHEA (47.80 ± 19.21 vs. 32.62 ± 15.96) and Beta-estradiol (59.36 ± 11.7 vs. 41.67 ± 10.59) levels decreased after the event. The significant decrease of DHEA (47.80 ± 19.21 vs. 32.11 ± 14.03) remained at 24 hours. Cortisol (200.38 ± 56.60 vs. 257.10 ± 74.00) and THE (238.65 ± 81.55 vs. 289.62 ± 77.13) increased after exercise and remained elevated 24 hours later (200.38 ± 56.60 vs. 252.48 ± 62.09; 238.65 ± 81.55 vs. 284.20 ± 66.66). The following anabolic/catabolic ratios fell after exercise: T/C (0.85 ± 0.54 vs. 0.54 ± 0.29), T/THE (0.66 ± 0.29 vs. 0.40 ± 0.08), T/THE+THF (0.38 ± 0.17 vs. 0.24 ± 0.06), DHEA/THE (0.22 ± 0.05 vs. 0.12 ± 0.05), DHEA/THF (0.34 ± 0.02 vs. 0.21 ± 0.01) and DHEA/THE+THF (0.12 ± 0.02 vs. 0.08 ± 0.03). The steroid profile showed that athletes were fatigued after finishing the competition and a catabolic state remained 24 hours later.